Análisis de máximas crecidas, para diferentes períodos de retorno, a través de métodos empíricos en la Cuenca superior del río Zamora (hoya de Loja). - Maza Medina, Jhuliana del Rocío (2024)
A maximum flood is defined as the peak flow that occurs in a basin as a result of heavy rainfall. The estimation of the maximum flow is important in the design of hydraulic works, especially for those protection works, which have the purpose of controlling the water coming from floods, which can cause material damage or loss of human lives. The objective of this research was to contribute with data of maximum floods for different return periods in the upper Zamora River basin. For this purpose, the physical and morphometric characterization of the Malacatos River micro-basin was carried out, and the estimation of maximum flows was done through empirical methods such as: rational and United States Soil Conservation Service (SCS) as well as hydrological methods such as the Triangular hydrograph methods, dimensionless of the CSC, the one proposed by Snyder, and the Ven Te Chow method. In the period March - December 2022, a series of gauging was carried out to establish a flow - water level relationship to generate the discharge curve of the microbasin, then the events of greater intensity were documented, in which the flow and the intensity of precipitation were recorded. The flows obtained by empirical methods were readjusted based on the intensity of precipitation and compared with the recorded flows, determining that the most representative events occurred on March 15th and December 30th, 2022, with intensities of 30,90 and 23,30 mm/h and flows of 72,80 and 54,23 m /s, respectively. Lastly, through the error percentage it was determined that the observed flows in the events are similar to the readjustment flows of the SCS Triangular and Dimensionless hydrographs methods, thus showing that these methods are adapted to the physical and morphometric conditions of the microbasin.